HUBUNGAN ANTARA PENGETAHUAN DENGAN SIKAP IBU HAMIL TENTANG MENJAGA PROTOKOL KESEHATAN PADA MASA PANDEMI COVID-19 DI PMB TITIN WIDYA NINGSIH PONTIANAK TAHUN 2021 - Susanna Susanna (JURNAL MEDIKA USADA, 2022)
ABSTRACT Background: COVID-19 was first announced by the World Health Organization (WHO) at the end of 2019 as an infectious disease caused by the Corona Virus (SARS-COV 2) (Zhong et al., 2020). On March 2nd 2020, for the first time the government has announced two cases of Covid-19 patients in Indonesia. Recently, it has been reported that it has attacked all age groups (infants, toddlers, adolescents, productive ages, and groups of pregnant women). The health protocols are consists of rules and regulations that need to be followed by all of us in order to be able to carry out activities safely during the COVID-19 pandemic. The results of a preliminary study at Independent Practice of Midwife Titin Widya Ningsih Pontianak by distributing questionnaires to 10 pregnant women found 6 people did not understand the knowledge and attitude to maintain health protocols during the Covid-19 Pandemic and 4 people understood. Objective: To find out the relationship between knowledge and mother's attitude about maintaining the health protocols during the Covid-19 pandemic at the Independent Practice of Midwife Titin Widya Ningsih Pontianak in 2021. Research Methods: The method that used in this study is a cross sectional approach. This research was conducted on 21 - 27 June 2021. The number of samples is 37 people. Results: Based on the research results, it is known that most of the respondents have good knowledge, namely 34 people (91.9%) of the total respondents. It also that most of the respondents have a positive attitude, namely agree and strongly agree as many as 30 people (81%) of the total respondents. Conclusion: From the results of the study, the researchers can conclude that there is a relationship between knowledge and behavior of pregnant women about maintaining the health protocols during the Covid-19 Pandemic at the Independent Practice of Midwife Titin Widya Ningsih Pontianak in 2021. Keywords: Knowledge, Attitude, Corona Virus, Health Protocols. Bibliography: 19 sources (2011 – 2021) Number of Pages: i – xv, 1-75